Expression of gp19K increases the persistence of transgene expression from an adenovirus vector in the mouse lung and liver. - Bruder, J T (1997)
Activation of the cellular immune system and subsequent lysis of vector-transduced cells by adenovirus- or transgene-specific cytotoxic T lymphocytes have been shown to limit transgene expression in animal models. The adenovirus gp19K gene product associates with major histocompatibility complex class I proteins and prevents their maturation by sequestering them in the endoplasmic reticulum. gp19K has been shown to block the ability of adenovirus-specific cytotoxic T lymphocytes to recognize virus-infected cells in vitro. To determine if gp19K expression in an adenovirus vector would increase transgene persistence, a vector that replaces the E1 region of adenovirus with an expression cassette encoding both gp19K and beta-glucuronidase was constructed. This vector produced high levels of functional gp19K in infected cells. RNase protection analysis revealed efficient expression of the gp19K gene in the mouse lung. Enhanced persistence and increased beta-glucuronidase activity were observed in the lung and liver following delivery of the gp19K-expressing adenovirus vector in B10.HTG mice but not in BALB/c mice. Since gp19K binds to both class I alleles on B10.HTG mice but only one allele on BALB/c mice, these results suggest that the major histocompatibility complex class I haplotype of mice is important in determining the effectiveness of gp19K in vivo. Since gp19K has previously been shown to interact with every human major histocompatibility complex class I allele tested, the inclusion of gp19K in gene therapy vectors may increase vector persistence in human gene therapy trials.